THE EFFECTIVENESS OF CURRICULUM OF ISLAMIC EDUCATION MANAGEMENT PROGRAM FOR ITS USERS AND STAKE HOLDER ( Critical Review towards the Curriculum of Study Program of Islamic Education Management of UNISNU Jepara ) - Haryanto Haryanto (Fakultas Tarbiyah dan Ilmu Keguruan, 2018)
This descriptive research aims at describing the effectiveness of curriculum of Islamic Education Management Postgraduate Program at UNISNU Jepara and contributing the critical review towards the corcordance of curriculum structure and subjects' variant offered connected to stake holder and the profession of users. Qualitative method is applied in this research, whereas the technique of selecting the subject of research is purposive sampling. The data of this research are collected through interview, observation, and documentation. The result shows that the variant of courses that are offered by the postgraduate program are categorized to be supporting enough for the concentration Islamic education supervisionin the case of education management  study program. However, some subjects need to be reviewed in curriculum review to enhance their effectiveness for users and stake holder of institutional and Islamic educationmanagement at UNISNU Jepara.   Penelitian deskriptif ini bertujuan menjelaskan keefektifan kurikulum manajemen pendidikan Islam perogram pascasarjana Unisnu Jepara dan memberikan kontribusi berupa tinjauan kritis terhadap kesesuaian dalam struktur kurikulum dan berbagai pihak yang berhubungan dengan pemangku kepentingan dan profesi para pemakainya. Penelitian ini menerapkan metode kualitatif, sedangkan teknik pemilihan data dengan menggunakan tehnik sampel terpilih. Data penelitian dikumpulkan melalui wawancara, observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa ragam mata kuliah yang ditawarkan dapat dikategorikan cukup mendukung konsentrasi supervisi pendidikan Islam dalam penjurusan program studi,namun sebagian mata kuliah perlu ditinjau ulang dalam tinjauan kurikulum untuk meningkatkan keefektifannya khususnya bagi para pemangku kepentingan lembaga dan manajemen pendidikan Islam UNISNU Jepara.